Soil Survey and Classification for Forest Use - Khan, M. A. Waheed; Yadav, J. S. P. (Indian Forester, 1962)
In view of the vast areas under forests, which constitute most vital asset of the country, it is essential to have a systematised knowledge of their soils through surveys. The data thus obtained will be of immense value in proper forest management, in land-use planning and in maximum production on a sustained basis. It bas been shown that on account of significant differences in the soil requirements the techniques of soil survey and classification for forestry purposes differ in many respects from those usually adopted for agriculture. Three broad types of soil surveys, namely, (1) Reconnaissance, (2) Detailed reconnaissance and (3) Detailed, have been mentioned. The techniques and procedure of soil survey to be used for forest areas have been described in detail. The prominent systems of soil classification in vogue have been elucidated. A brief account has been given of the methods of soil surveys being followed in some European countries and of the more important developments that have taken place in soil survey and classification, particularly of agricultural lands in India. Since our present knowledge about forest soils is very poor, it is suggested that concerted efforts should be made in this aspect of soil research. It is hoped that with the establishment of several regional research centres and State laboratories and with the strengthening of technical staff at Forest Research Institute, a good headway will be made in this direction and some tangible results of practical value will be achieved.